FORMING OF PSALMS IN CONTEXT HISTORY WORLD VIEW - Yaroshenko, R. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article analyzes the development of psalms through literary and historical outlook, clearly outlined his division and classification. The author demonstrates the key categories of the genre psalm, its influence on ancient Ukrainian literature creates cultural and philosophical discourse. He vividly describes the features of form, content, writing and the genesis of the literary world view that is now under the current point of view of many literary scholars.